Hydrogen Economy as a Driver of Synergetic Technological Development: Policy and Application Evidence from Russia - Salnikova, Anastaisa (International Journal of Energy Economics and Policy, 2022)
Hydrogen energy is still at an early stage of development: Nevertheless, national and international strategies are used to boost its development by all kinds of incentives, subsidies, tax instruments and R&D financing of pilot projects in order to achieve the main goals: decarbonization of the energy sector, ensuring the reliability of supply of energy systems. The technical capabilities of decarbonization are still coexisting with high production costs, difficulties in storing and delivering hydrogen to consumers. Shift to hydrogen economy is not possible without thorough consideration of policies at different levels as well as technological advances. In this article the author analyses current situation of Russian hydrogen economics from strategic and technological point of view. The main agenda-setting documents and contributors in the field of technical deployment of hydrogen projects have been analyzed by applying content-analysis. Main policy implications and recommendations have also been given.